Sexualized Violence is a Citizenly Issue: Neoliberalism, the Affective Economy of Fear and Fighting Approaches to Sexualized Violence Prevention - Shewan, Kascindra Ida Sadie (Atlantis)

(untitled) (Mount Saint Vincent University, 2018)
This paper investigates how Western forms of citizenship, formed and informed by (neo)liberal ideologies of governance, mediate strategies for sexualized violence prevention. Focusing on one sexualized violence prevention strategy, what I term “the fighting approach,” I argue that the successes and failures of sexualized violence prevention are contingent upon their commensurability with, and amenability to, the goals of broader sociopolitical systems and discourses of belonging: namely, classical liberal and neoliberal ideals of the citizen.